What Difference Does a Robot Make? The Material Enactment of Distributed Coordination - Beane, Matt; Orlikowski, Wanda J. (Organization Science, 2015)
What difference does robotic telepresence make to the coordination of complex, dynamic, and distributed knowledge work? We explored this question in a post-surgical intensive care unit where medical workers struggled to coordinate their work in the face of different assessments of their extremely sick patients. Our in-depth field study examined night rounds, a central routine for coordinating work in this unit that was performed remotely through different technologies. We found that night rounds that are materially enacted through robotic telepresence intensify coordination outcomes both positively and negatively, resulting in contrary implications for subsequent coordination of work. We further found that these differences in intensification depend on whether preparatory work is more or less distanced from the bedside. We develop a theoretical account of these findings by explaining how the coordination of complex, dynamic, and distributed work is crucially related to how that work is materially enacted over time.